Hollow-walled lattice materials by additive manufacturing: Design, manufacture, properties, applications and challenges. Issue 5 (October 2021) - Noronha, J.; Qian, M.; Leary, M.; Kyriakou, E.; Brandt, M.
Graphical abstract: Highlights: Fabrication processes, materials, and achievable geometrical parameters are explored. The reported mechanical properties and unique deformation responses are assessed. Discrepancies within specific unit cell definitions are discovered. Applications and future outcomes for hollow-walled lattices are recommended. The Gibson-Ashby predictive model is assessed for hollow-walled lattices. Abstract: The rapid growth of additive manufacturing (AM) technologies has enabled the emergence of geometrically sophisticated materials or structures with tailored and/or enhanced mechanical responses. In addition to dense-walled lattice structures, innovation within the past decade has identified that hollow-walled lattice topologies exhibit the multifaceted potential of competitive strength and rigidity, whilst displaying unique deformation behaviours, indicating that they may be an important subsequent step in lattice evolution. Hollow-walled sections facilitate density and geometrical parameters well below what is achievable by dense-walled sections, providing additional hierarchies of architecture at micrometre to even nanoscale proportion. Their wall thickness can range from 20 nm to 800 µm while the relative density can span three orders of magnitude between 0.01% and 30%. Despite nearly a decade of research into hollow-walled lattice topologies, no meta-analysis exists to provide an informative overview of these structures. This research addresses this deficiency and provides a data-driven review of hollow-walled lattice materials. It elucidates how these hollow-walled lattices deviate from the current limitations of dense-walled lattices and the underlying mechanisms that dictate their performance, with data accumulated from an exhaustive collection of literature sources. A range of new insights into their design and manufacture is discussed for their future research and applications in different engineering fields.